Effectiveness of a health intervention based on WHO food safety manual in Iran - Mohtasham Ghaffari; Yadollah Mehrabi; Sakineh Rakhshanderou; Ali Safari-Moradabadi; Seyyede Zenab Jafarian (BMC, 2020)
Abstract Background Food safety manual was developed by the World Health Organization (WHO) to train professionals to reduce the burden of foodborne diseases as a global strategy. The present pioneering research aimed to explore the effectiveness of an intervention based on the manual of five keys to safer food by WHO in enhancing the knowledge, attitude and behavior of Iranian Female Community Health Volunteers (FCHVs). Methods In the present quasi-experimental research, FCHVs (n = 125) were selected and assigned to two groups, an intervention and a control. A modified version of the questionnaire based on WHO manual was used to measure knowledge, attitude and behavior of the sample. The questionnaire was first completed at the outset of the study (pre-test) and then once again in 2 months of the intervention (post-test). Face and content validity of the questionnaire was tested and confirmed. Cronbach's alpha was used to test the reliability of the questionnaire along with the test-retest method of testing reliability. The data entered SPSS16 for statistical analysis. To this aim, Chi-squared test, dependent and independent samples T-test, ANOVA and ANCOVA were run. Partial population attributable risks were calculated and corresponding 95% confidence intervals (95% CIs) were estimated using a bootstrap method. Results The two groups showed no statistically significant difference in the pretest (p > .05). In the post-test, the mean scores for all variables was higher in the intervention group than the control, and this difference between the two research groups was statistically significant (p < .001). When the volunteers were adjusted for age and experience in healthcare centers, the mean scores were significantly higher in the intervention group than the control (p < .001). Conclusion It was revealed in the present study that the educational intervention based on five keys to food safety manual by WHO managed to improve participants' knowledge, attitude and behavior. Translation of the target guideline in future can be a great help to researchers in prospective research. Trial Registration Retrospectively registered: Iranian Registry of Clinical Trials IRCT20160822029485N4 , at 2020-03-16.